2021
DOI: 10.26434/chemrxiv.13606055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amyloid β-binding Bifunctional Chelators with Favorable Lipophilicity for 64Cu PET Imaging in Alzheimer’s Disease

Abstract: Herein we report a new series of bifunctional chelators (BFCs) with high affinity for amyloid aggregates, strong binding affinity towards Cu(II) and favorable lipophilicity for potential blood-brain barrier (BBB) penetration. The alkyl carboxylate pendant arms offer up to three orders of magnitude higher binding affinity towards Cu(II) vs. the parent chelating fragment, and can generate fairly stable Cu complexes, including <sup>64</sup>Cu-radiolabeled compounds. Among the five compounds tested, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…These results suggest that 64 Cu-bis-HYR-8 may take a longer time to reach the brain, possibly given its larger molecular weight and a slower passive diffusion through the BBB. Overall, the brain uptake of these developed 64 Cu complexes is slightly lower than those of the complexes we reported previously 22,38,50,51 or the 64 Cu-GTSM 52,53 or 64 Cu-ATSM 14 derivatives reported by Blower et al and Donnelly et al, respectively, probably because of the neutral nature of these chelators that cannot balance the positive charge of the Cu 2+ ion and thus limits the BBB permeability of the Cu complexes. However, the surprising increase over time in brain uptake and somewhat limited rapid liver and kidney clearance observed for 64 Cu-bis-HYR-8, which is different from what was observed for "free" 64 Cu acetate, 52,53 suggests that the bis-HYR-8 ligand framework, upon further derivatization, may support Cu complexes that are kinetically stable in vivo.…”
Section: ■ Results and Discussioncontrasting
confidence: 63%
“…These results suggest that 64 Cu-bis-HYR-8 may take a longer time to reach the brain, possibly given its larger molecular weight and a slower passive diffusion through the BBB. Overall, the brain uptake of these developed 64 Cu complexes is slightly lower than those of the complexes we reported previously 22,38,50,51 or the 64 Cu-GTSM 52,53 or 64 Cu-ATSM 14 derivatives reported by Blower et al and Donnelly et al, respectively, probably because of the neutral nature of these chelators that cannot balance the positive charge of the Cu 2+ ion and thus limits the BBB permeability of the Cu complexes. However, the surprising increase over time in brain uptake and somewhat limited rapid liver and kidney clearance observed for 64 Cu-bis-HYR-8, which is different from what was observed for "free" 64 Cu acetate, 52,53 suggests that the bis-HYR-8 ligand framework, upon further derivatization, may support Cu complexes that are kinetically stable in vivo.…”
Section: ■ Results and Discussioncontrasting
confidence: 63%
“…14 These BFCs and their Cu complexes have shown midnanomolar affinity for amyloid plaques, 22,24,25 in comparison to the 6.7 nM K i of 18 F-florbetaben. 14 We have also previously reported BFCs with high stability constants for their Cu complexes, approaching values similar to 1,4,7-triazacyclononane-1,4,7-triacetic acid (NOTA), 21,26,27,29 thus indicating that the class of TACN-based BFCs is promising in the development of 64 Cu PET imaging agents for AD. Despite the promise of these complexes, further optimization of at least one of the three properties described above is required for each ligand system prior to further investigation.…”
Section: ■ Introductionmentioning
confidence: 75%
“…Our group demonstrated that phenol with Me 2 TACN or other TACN derivatives are able to chelate 64 Cu efficiently and strongly. [52][53][54] However, the Cu chelating abilities of phenol with two TACN groups attached have never been investigated. Job's plots were first performed to analyze the stoichiometry of the Cu(II)−ligand in solution.…”
Section: Cu Chelating Abilities Of the Amphiphilic Dcm-rbfsmentioning
confidence: 99%